FungalBraid 2.0: expanding the synthetic biology toolbox for the biotechnological exploitation of filamentous fungi - Moreno-Giménez, Elena; Gandía, Mónica; Sáez, Zara; Manzanares, Paloma; Yenush, Lynne; Orzáez, Diego; Marcos, Jose F.; Garrigues, Sandra (Frontiers in Bioengineering and Biotechnology, 2023)
Fungal synthetic biology is a rapidly expanding field that aims to optimize the biotechnological exploitation of fungi through the generation of standard, ready-to-use genetic elements and universal syntax and rules for contributory use by the fungal research community. Recently, an increasing number of synthetic biology toolkits have been developed and applied to filamentous fungi, which highlights the relevance of these organisms in the biotechnology field. The FungalBraid (FB) modular cloning platform enables interchangeability of DNA parts with the GoldenBraid (GB) platform designed for plants and other systems compatible with the standard Golden Gate cloning and syntax, and uses binary pCAMBIA-derived vectors to allow Agrobacterium tumefaciens-mediated transformation of a wide range of fungal species. In this study, we have expanded the original FB catalog by adding 27 new DNA parts that we have functionally validated in vivo. Among these are the resistance selection markers for the antibiotics phleomycin and terbinafine, as well as the uridine auxotrophy marker pyr4. We also used a normalized luciferase reporter system to validate several promoters, namely PpkiA, P7760, Pef1α, PafpB constitutive promoters, and the PglaA, PamyB and PxlnA inducible promoters.Additionally, the recently developed dCas9-regulated GB_SynP synthetic promoter collection for orthogonal CRISPR activation (CRISPRa) in plants has been adapted to fungi through the FB system. In general, the expansion of the FB catalog is of great interest for the scientific community since it expands the number of possible modular and interchangeable DNA assemblies, exponentially increasing the possibilities of studying, developing and exploiting filamentous fungi.